Dark Mountain: scenography for the end of the world and a more-than-human future. Issue 3 (2nd October 2021) - Kelly, Kathryn; Rixon, Tessa; Neideck, Jeremy; Pike, Shane; Brumpton, Anthony
ABSTRACT : Weaving together the collective experience of several Australian scenographers and dramaturgs, this article examines how performance-making practices and scenographic design processes can be reshaped by our deepening understanding of the ecology that surrounds us. As practitioner-scholars, we are trying to consider how new 'practice actions' in scenography can be increasingly ecologically responsive. This is a very particular endeavour in Australia where landscape is contested, First Nations claims are ignored, and denial of the climate emergency is official government policy. Over a decade ago, British artists and environmental activists Paul Kingsnorth and Dougald Hine founded the Dark Mountain project by publishing a Manifesto that warned of an impending, headlong rush into the abyss of ecocide. Heeding their call as our starting provocation, this article offers two case studies that demonstrate possible ecoscenographic approaches in Australian performance-making. While the case studies raise as many questions as they provide answers, they demonstrate how keeping environmentalism at the forefront of creativity can help us shape a more-than-human future in an ecologically fragile world.